Transformasi Digital Guru Ekonomi di Era Education 5.0: Studi Kasus Literasi Digital dan Praktik Reflektif pada SMA di Kabupaten Minahasa - Allen A. Ch. Manongko; Listriyanti Palangda (Lembaga Teewan Journal Solutions, 2026)
Digital transformation in education drives a paradigm shift toward Education 5.0, integrating technology and human values in learning. Economics teachers are required not only to use technology but also to integrate it pedagogically and reflectively. This study aims to analyze economics teachers' digital literacy characteristics, identify reflective practices in technology integration, and uncover supporting and inhibiting factors for digital teacher transformation in high schools in Minahasa Regency. This qualitative study used an exploratory case study design. Informants were selected purposively involving economics teachers and principals. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña through thematic coding. Data validity was ensured through source triangulation, technical triangulation, and member checking. The results indicate that teachers' digital literacy has diverse characteristics. Reflective practice plays an important role in evaluating and developing technology-based learning. Digital teacher transformation is influenced by supporting factors (school support, professional collaboration, and digital self-efficacy) and inhibiting factors (technostress, intergenerational digital divide, and technically oriented training). This study shows that teacher digital transformation is a multidimensional process influenced by individual, social, and institutional factors in supporting adaptive learning based on Education 5.0.